Theories of literature - Peer, Willie van (Primerjalna književnost, 2014)
Starting from a categorization by Robert Penrose, the question is asked in what sense literary theories might be called "scientific". It turns out that, seen from this vantage point, few of the extant theories deserve the name "scientific". This is all the more surprising, because the methodology for developing such scientific theories is available to anyone interested in the matter. This is illustrated positively with reference to the theory of "foregrounding". At the same time, it is shown how feminist literary theories fall utterly short of reaching their own aims, by refraining to do empirical research.
Keywords: literarna teorija; literary theory; znanstvenost; empirična literarna veda; metodologija; teorija aktualizacije; feministična literarna veda